School readiness of children at high risk of cerebral palsy randomised to early neuroprotection and neurorehabilitation: protocol for a follow-up study of participants from four randomised clinical trials. Issue 2 (27th February 2023) - Boyd, Roslyn N; Novak, Iona; Morgan, Catherine; Bora, Samudragupta; Sakzewski, Leanne; Ware, Robert S; Comans, Tracy; Fahey, Michael Collingwood; Whittingham, Koa; Trost, Stewart; Pannek, Kerstin; Pagnozzi, Alex; et al.
Abstract : Introduction: School readiness includes cognitive, socio-emotional, language and physical growth and development domains which share strong associations with life-course opportunities. Children with cerebral palsy (CP) are at increased risk of poor school readiness compared with their typically developing peers. Recently, earlier diagnosis of CP has allowed interventions to commence sooner, harnessing neuroplasticity. First, we hypothesise that early referral to intervention for children at-risk of CP will lead to improved school readiness at 4–6 years relative to placebo or care as usual. Second, we hypothesise that receipt of early diagnosis and early intervention will lead to cost-savings in the form of reduced healthcare utilisation. Methods and analysis: Infants identified as at-risk of CP ≤6 months corrected age (n=425) recruited to four randomised trials of neuroprotectants (n=1), early neurorehabilitation (n=2) or early parenting support (n=1) will be re-recruited to one overarching follow-up study at age 4–6 years 3 months. A comprehensive battery of standardised assessments and questionnaires will be administered to assess all domains of school readiness and associated risk factors. Participants will be compared with a historical control group of children (n=245) who were diagnosed with CP in their second year of life. Mixed-effects regression models will be used to compare school readiness outcomes between those referred for early intervention versus placebo/care-as-usual. We will also compare health-resource use associated with early diagnosis and intervention versus later diagnosis and intervention. Ethics and dissemination: The Children's Health Queensland Hospital and Health Service, The University of Queensland, University of Sydney, Monash University and Curtin University Human Research Ethics Committees have approved this study. Informed consent will be sought from the parent or legal guardian of every child invited to participate. Results will be disseminated in peer-reviewed journals, scientific conferences and professional organisations, and to people with lived experience of CP and their families. Trial registration number: ACTRN12621001253897.